Geomagnetic sudden commencements observed at the Syowa-Iceland conjugate stations - Nagano, Hiroshi; Araki, Tohru; Iyemori, Toshihiko; Fukunishi, Hiroshi; Sato, Natsuo; Ayukawa, Masaru (1987)
P(論文) In order to clarify characteristics of geomagnetic sudden commencements (SC's) at geomagnetically conjugate stations, six SC events were analyzed by the use of digital magnetic data at Syowa Station in Antarctica and Husafell, Isafjordur and Tjornes in Iceland during the interval from September 1984 to January 1985. SC polarization, waveforms and SC-associated pulsations are examined between the conjugate stations, and the characteristics are discussed in comparison with a model (H. NAGANO et al. : Mem. Natl Inst. Polar Res., Spec. Issue, 36,123,1985) suggested for the latitudinal reversal of SC polarization in high latitudes on the ground. departmental bulletin paper